Present status and challenges of underwater acoustic target recognition technology: A review - Zhufeng, Lei; Xiaofang, Lei; Na, Wang; Qingyang, Zhang (Frontiers in Physics, 2022)
Future naval warfare has placed high demands on underwater targets' target detection, target recognition, and opposition resistance, among other things. However, the ocean's complex underwater acoustics environment and evolving "stealth" technology of underwater targets pose significant challenges to target detection systems, which has become a hot topic in the field of underwater acoustics signal processing in various countries. This paper introduced the mechanism of underwater target radiation noise generation, analyzed the research progress and development of underwater target radiation noise recognition by applying machine learning from three perspectives: signal acquisition, feature extraction, and signal recognition at home and abroad, and elaborated on the challenges of underwater target radiated noise recognition technology against the backdrop of rapid computing science development, and finally discussed the solutions and development trend of these challenges.